ECO-RELIGIOUS TOURISM BASED ON SAUJANA IN TURGO-MERAPI TOURISM VILLAGE - Sugiarto, Eko; Makiya , Kiki Rizki; Irawati , Novi (PT. Jurnal Center Indonesia Publisher, 2025)
The purpose of this study is to explain the eco-religious tourism model in the Turgo-Merapi Tourism Village area which is part of the Gunung Merapi National Park (GMNP) in Indonesia. This study uses a descriptive-qualitative method to explore the implementation of ecotourism and religious tourism concepts in the Turgo-Merapi Tourism Village area. The data collected are primary and secondary. Primary data were collected through observation and interviews, secondary data were collected through document studies. The results of the study indicate that eco-religious tourism based on saujana is a model that is considered to be able to link tourism developments planned in local government policy (ecotourism) and developments occurring in the field (religious tourism) as well as accommodating the economic and conservation interests. Eco-religious tourism based on saujana model provides a broad idea that not only has a positive impact on environmental conservation, but also strengthens the social, cultural, and spiritual aspects of communities in areas that still practice religious values. This research is still limited to the southern side of GMNP which is located in Sleman Regency, Special Region of Yogyakarta. Further research is needed with the same theme in Magelang Regency, Boyolali Regency, and Klaten Regency so that it can complete the results of this study.